PARTISIPASI MASYARAKAT DALAM MENDUKUNG WISATA TELUK KILUAN KABUPATEN TANGGAMUS - Dewi, Tribuana Shinta; Affandi, Muhammad Irfan; Izhar, Ryansyah (Jurnal Perencanaan dan Pengembangan Kebijakan, 2024)
Kiluan Negeri Village based on Regional Regulations of Lampung Province and Tanggamus Regency refers to the concept of ecotourism and Community-Based Ecotourism in tourism development. The purpose of this study was to identify the development of community participation in supporting Kiluan Bay tourism in Pekon Kiluan Negeri, Kelumbayan District, Tanggamus Regency. The objectives of this study are 1) Standardization Criteria for Existing Conditions for Community Improvement in Pekon Kiluan Negeri Tourism Development based on 4 Tourism Components (attraction, accessibility, amenities and ancillary); 2) represents the level of community participation in the development of Teluk Kiluan Tourism, Kelumbayan District, Tanggamus Regency. The method used is Qualitative Descriptive Analysis (descriptive method). The results obtained 1) Two-way participation has occurred between the government and local communities in various tourism component sectors (attractions, accessibility, amenities and supports). 2) According to the theory of Arnstein (1969) at the level of Citizen Power and the 6th ladder partnerships (partnerships) there are obstacles in community participation.